IMPORTANCE OF PAIN DURATION PRIOR PAIN RELIEF TREATMENT WITH CT-GUIDED PERIRADICULAR THERAPY IN PATIENTS WITH CHRONIC LUMBAR PAIN - Veljanovski, Dimitar; Prgova, Biljana; Kostova, Masha; Ristikj-Stomnaroska, Daniela; Dejanova, Sandra; Vasilevska Nikodinovska, Violeta (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
CT-guided periradicular therapy (PRT) is a minimally invasive interventional technique for treatment of chronic lumbar pain. Aim: To investigate importance of pain duration before PRT treatment in patients with chronic lumbar pain and radiculopathy, with clinical effectiveness assessment. A prospective follow-up CT guided PRT study was done in 166 patients divided into 4 groups according duration of pain before intervention (<3 months, 4-6months, 7-12months, >1year). Degree of pain intensity was determined according to VAS scale. Improvement degree was excellent, good, moderate, or weak.Good clinical response was defined when improvement is greater or equal to 50% on VAS scale, and functional improvement was equal to 40% in the reduction of the ODI index. Follow-up was done at 2nd weeks, 3 and 6 months. Good response was observed in 51.8% of the cases after 2 weeks, 54.2% after 3 months and 59% after 6 months. ODI index parameters was greater or equal to 40% in 22.2% after 2 weeks, 13.8% after 3 months, and 8.4% after 6 months.After 6 months in patients with pain duration up to 3 months, the improvement was excellent in 41(74.5%), moderate in 3(5.4%), good in 6(10.9%) and weak in 4(7.2%) patients in contrast to patients with pain over one year who showed excellent improvement in only 2(5.7%) patients, moderate in 11(31.4%), good in 6(17.1%) and weak in 16 (45.7%) patients. PRT is clinically effective with better clinical outcomein patients with shorter duration of symptoms. Keywords : chronic lumbar pain, radiculopathy, CT guided, interventional, steroids https://doi.org/10.55302/JMS2142094v